Are the literacy difficulties that characterize developmental dyslexia associated with a failure to integrate letters and speech sounds?. Issue 4 (6th August 2016) - Nash, Hannah M.; Gooch, Debbie; Hulme, Charles; Mahajan, Yatin; McArthur, Genevieve; Steinmetzger, Kurt; Snowling, Margaret J.
Abstract: The 'automatic letter‐sound integration hypothesis' (Blomert, 2011 ) proposes that dyslexia results from a failure to fully integrate letters and speech sounds into automated audio‐visual objects. We tested this hypothesis in a sample of English‐speaking children with dyslexic difficulties ( N  =   13) and samples of chronological‐age‐matched (CA; N = 17) and reading‐age‐matched controls (RA; N  =   17) aged 7–13 years. Each child took part in two priming experiments in which speech sounds were preceded by congruent visual letters (congruent condition) or Greek letters (baseline). In a behavioural experiment, responses to speech sounds in the two conditions were compared using reaction times. These data revealed faster reaction times in the congruent condition in all three groups. In a second electrophysiological experiment, responses to speech sounds in the two conditions were compared using event‐related potentials (ERPs). These data revealed a significant effect of congruency on (1) the P1 ERP over left frontal electrodes in the CA group and over fronto‐central electrodes in the dyslexic group and (2) the P2 ERP in the dyslexic and RA control groups. These findings suggest that our sample of English‐speaking children with dyslexic difficulties demonstrate a degree of letter‐sound integration that is appropriate for their reading level, which challenges the letter‐sound integration hypothesis. Abstract : We tested the hypothesis that dyslexia results from a failure to fully integrate letters and speech sounds into automated audio‐visual objects by collecting behavioural and ERP data during a priming task. Our data suggest a developmental shift in typically developing children driven by reading experience and that English speaking children with dyslexia have developed a degree of integration that is at least in line with their reading level. This finding challenges the hypothesis.